2022
DOI: 10.1111/mec.16611
|View full text |Cite
|
Sign up to set email alerts
|

Upwelling‐level acidification and pH/pCO2 variability moderate effects of ocean acidification on brain gene expression in the temperate surfperch, Embiotoca jacksoni

Abstract: Acidification‐induced changes in neurological function have been documented in several tropical marine fishes. Here, we investigate whether similar patterns of neurological impacts are observed in a temperate Pacific fish that naturally experiences regular and often large shifts in environmental pH/pCO2. In two laboratory experiments, we tested the effect of acidification, as well as pH/pCO2 variability, on gene expression in the brain tissue of a common temperate kelp forest/estuarine fish, Embiotoca jacksoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 104 publications
(172 reference statements)
0
5
0
Order By: Relevance
“…In fish nervous tissue, OA exposure has variable effects on GABA A R subunit transcript expression, causing upregulation in some species [ 26 , 30 ] but not another [ 31 ]. Furthermore, differences in OA exposure duration [ 25 , 26 , 28 ] and magnitude [ 29 ] are associated with variable effects on the expression of genes coding for GABA A R subunits within species. In I. pygmaeus , we found small, coordinated downregulation in the CNS and upregulation in the eyes of genes for ion-channel receptors, which included GABA A receptor subunit transcripts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fish nervous tissue, OA exposure has variable effects on GABA A R subunit transcript expression, causing upregulation in some species [ 26 , 30 ] but not another [ 31 ]. Furthermore, differences in OA exposure duration [ 25 , 26 , 28 ] and magnitude [ 29 ] are associated with variable effects on the expression of genes coding for GABA A R subunits within species. In I. pygmaeus , we found small, coordinated downregulation in the CNS and upregulation in the eyes of genes for ion-channel receptors, which included GABA A receptor subunit transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is less research assessing the transcriptomic response of nervous tissue to elevated CO 2 . Recently, studies have examined the transcriptomic response of the fish nervous system to elevated CO 2 conditions, including in coral reef fishes [ 24 28 ], temperate marine fishes [ 21 , 29 , 30 ] and ocean-phase salmon [ 31 ]. In marine invertebrates, two transcriptomic studies assessing the whole-body response of pteropod molluscs to elevated CO 2 identified altered expression of genes involved in nervous system function [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fish nervous tissue, OA exposure has variable effects on GABA A R subunit transcript expression, causing upregulation in some species (Cohen-Rengifo et al, 2022;Schunter et al, 2018) but not another (Williamset al, 2019). Furthermore, differences in OA exposure duration (Kang et al, 2022;Schunter et al, 2018;Schunter et al, 2016) and magnitude (Toy et al, 2022) are associated with variable effects on the expression of genes coding for GABA A R subunits within species. In I. pygmaeus, we found small, coordinated downregulation in the CNS and upregulation in the eyes of genes for ion-channel receptors, which included GABA A receptor subunit transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is less research assessing the transcriptomic response of nervous tissue to elevated CO 2 . Recently, studies have examined the transcriptomic response of the fish nervous system to elevated CO 2 conditions, including in coral reef fishes (Kang et al, 2022;Schunter et al, 2021;Schunter et al, 2019;Schunter et al, 2018;Schunter et al, 2016), temperate marine fishes (Cohen-Rengifo et al, 2022;Porteus et al, 2018;Toy et al, 2022) and ocean-phase salmon (Williams et al, 2019). In marine invertebrates, two transcriptomic studies assessing the whole-body response of pteropod molluscs to elevated CO 2 identified altered expression of genes involved in nervous system function (Johnson & Hofmann, 2017;Moya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This is important because ecological complexity can buffer negative impacts of climate stressors such as those observed in more simplified laboratory systems [66]. Moreover, natural variability (e.g., daily, seasonally) of climate stressors-which is mimicked at natural analogues-is known to alter species responses to climate stress (e.g., diminished fish gene expression in Embiotoca jacksoni compared to stable stressor conditions [177]). Especially for species with restricted home ranges, these analogues allow insights into the integrated ecological responses of fishes to climate change stressors, responses like epigenetic adaptation, behavioural modifications, physiological acclimatization, phenological responses, demographic changes, range shifts, species interactions, habitat regime shifts, and natural selection, all of which combine to explain how communities, ecosystems, and biodiversity might be reshaped directly and indirectly by environmental change [178].…”
Section: Natural Analogues That Incorporate Ecological Complexitymentioning
confidence: 99%